Research on the preparation and properties of foamed PP/wood flour composites - Suwei Wang; Ke Chen; Ping Xue; Mingyin Jia (Materials Research Express, 2020)
In order to improve the toughness of the wood-polymer composites, the microcellular structure was introduced to the polypropylene (PP) based wood-polymer composites by the technology of continuous extrusion in this article. In order to improve the mechanical and thermal properties of the samples further, the content of both wood flour (WF) and the chemical blowing agent were investigated. Besides, the compound foaming agents were also applied in the process of extrusion. According to the experimental results, the addition of WF contributed to increase both the softening temperatures and the apparent densities of the samples, and the best mechanical properties and microcellular structure were obtained when the mass ratio of WF to PP increased to 3/7. In addition, compared with the granular blowing agent, the powdered foaming agent showed a great advantage in dispersion, which helped to improve the bubble morphology and the mechanical strengths of the samples. Furthermore, the minimum bubble size and the maximum bubble density were both achieved at the powder content of 1 phr.